The Legal System of Gene Therapy Contracts - Khudair, Dr. Muhannad Othman (Thi Qar Arts Journal, 2024)
Gene therapy plays a crucial role in diagnosing and detecting genetic diseases, preventing them, and treating them with modern methods. Most genetic diseases are caused by defective recessive genes, which can be replaced with healthy genes that perform the same function as the defective ones. This has enabled the treatment of many diseases, such as heart and vascular diseases, cancerous tumors, neurological diseases, viral hepatitis, diabetes, and congenital birth defects, among others.Gene therapy is the central focus of the treatment contract, which is based on the will of the parties involved and their hope for recovery through the latest precise scientific methods humanity has reached. Therefore, the gene therapy contract differs from the medical contract in many characteristics that make it distinct from other medical contracts. It is a complex, formal, civil, real, bilateral, personal, continuous, and specific contract. Despite this, the civil law has not established specific provisions for it.Thus, a doctor’s breach of obligations arising from the gene therapy contract results in liability and compensation for the damage caused to the patient due to the doctor’s error. Compensation has two interests: the interest of the injured party, which requires that the compensation be proportional to the damage suffered, and the interest of the doctor, which requires that the compensation be determined in a way that does not overburden the doctor and hinder their ability to continue their practice and keep up with medical developments.This research aims to clarify the concept of the gene therapy contract and its applications, as well as to explain the characterization of the gene therapy contract, the liability arising from a doctor’s breach of obligations under the contract, the conditions for establishing liability, and the compensation for the damage suffered by the injured patient.The study is divided into two sections: the first section reviews the concept of the gene therapy contract, and the second section discusses the impact of breaching the gene therapy contract.